Memorandum of Understanding between the University of Windsor, Canada and BRAC University, Bangladesh (2002) - The University of Windsor; BRAC University (University of Windsor and BRAC University, 2013)
Educational accord between the university of Windsor, Canada and BRAC University, Bangladesh.